2014
DOI: 10.1080/87565641.2014.906602
|View full text |Cite
|
Sign up to set email alerts
|

Carving the World for Language: How Neuroscientific Research Can Enrich the Study of First and Second Language Learning

Abstract: Linguistics, psychology, and neuroscience all have rich histories in language research. Crosstalk among these disciplines, as realized in studies of phonology, is pivotal for understanding a fundamental challenge for first and second language learners (SLLs): learning verbs. Linguistic and behavioral research with monolinguals suggests that infants attend to foundational event components (e.g., path, manner). Language then heightens or dampens attention to these components as children map word to world in lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Of interest to the study of CSSL, these patterns yield lexicalization biases, or assumptions regarding how words map onto relations in events (e.g., George et al, 2014;Göksun et al, 2010;Shafto et al, 2013). When presented with a novel verb, Spanish speakers will be more likely to associate the verb with path of motion, while an English speaker will map it onto manner of motion.…”
Section: Cssl and Lexicalization Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest to the study of CSSL, these patterns yield lexicalization biases, or assumptions regarding how words map onto relations in events (e.g., George et al, 2014;Göksun et al, 2010;Shafto et al, 2013). When presented with a novel verb, Spanish speakers will be more likely to associate the verb with path of motion, while an English speaker will map it onto manner of motion.…”
Section: Cssl and Lexicalization Biasesmentioning
confidence: 99%
“…However, by the preschool years, children favored the lexicalization pattern of their native language (see also Hohenstein, 2005). Such shifts are part of a larger process of semantic reorganization, in which infants learn to attend to an array of relations in events underlying the world's languages, before shifting to language specific biases through language exposure (George et al, 2014;Göksun et al, 2010).…”
Section: Cssl and Lexicalization Biasesmentioning
confidence: 99%
“…Furthermore, it has been argued that the particular event structure as expressed by verb predicates can affect how events are mentally represented (e.g. George et al, 2014;Göksun et al, 2010Göksun et al, , 2017Gerwien & von Stutterheim, 2018;Slobin, 2006). For example, Skordos et al (2020) recently found that the semantics of motion verbs (lexicalising manner or path of motion) interacted with how well people remembered changes in event features related to either the manner or the goal of motion; showing that the meaning of a verb predicate presented to or produced by people can affect event memory.…”
Section: Events In Languagementioning
confidence: 99%
“…The first is what we deem an event primary hypothesis. To use different force dynamics verbs (e.g., Cause: cause, make; Enable: help, allow; Prevent: keep, stop), children might first need to differentiate and conceptualize the various causal events represented by force dynamics (George 2014;George, Göksun, Hirsh-Pasek, & Golinkoff, 2014;Göksun, Hirsh-Pasek, & Golinkoff, 2010;Wagner & Lakusta, 2009;Wolff 2003Wolff , 2007Wolff, Klettke, Ventura, & Song, 2005;Wolff & Song, 2003;Wolff, Song, & Driscoll, 2002). Therefore, language may be related to physical reasoning in that Inferences about Force and Motion 26 language builds on those aspects of events that are most easy to reason about (i.e., forces acting in a single dimension).…”
Section: Questions For Further Researchmentioning
confidence: 99%